STING Is Required in Conventional Dendritic Cells for DNA Vaccine Induction of Type I T Helper Cell- Dependent Antibody Responses - Ulrich-Lewis, Justin Theophilus; Draves, Kevin E.; Roe, Kelsey; O’Connor, Megan A.; Clark, Edward A.; Fuller, Deborah Heydenburg (Frontiers in Immunology, 2022)
DNA vaccines elicit antibody, T helper cell response and effector CD8+ T cell responses. Currently, little is known about the mechanism that DNA vaccines employ to induce adaptive immune responses. Prior studies have demonstrated that stimulator of interferon genes (STING) and conventional dendritic cells (cDCs) play critical roles in DNA vaccine induced antibody and T cell responses. STING activation by double stranded (dsDNA) sensing proteins initiate the production of type I interferon (IFN), but the DC-intrinsic effect of STING signaling is still unclear. Here, we investigated the role of STING within cDCs on DNA vaccine induction of antibody and T cell responses. STING knockout (STING-/-) and conditional knockout mice that lack STING in cDCs (cDC STING cKO), were immunized intramuscularly with a DNA vaccine that expressed influenza A nucleoprotein (pNP). Both STING-/- and cDC STING cKO mice had significantly lower type I T helper (Th1) type antibody (anti-NP IgG2C) responses and lower frequencies of Th1 associated T cells (NP-specific IFN-γ+CD4+ T cells) post-immunization than wild type (WT) and cDC STING littermate control mice. In contrast, all mice had similar Th2-type NP-specific (IgG1) antibody titers. STING-/- mice developed significantly lower polyfunctional CD8+ T cells than WT, cDC STING cKO and cDC STING littermate control mice. These findings suggest that STING within cDCs mediates DNA vaccine induction of type I T helper responses including IFN-γ+CD4+ T cells, and Th1-type IgG2C antibody responses. The induction of CD8+ effector cell responses also require STING, but not within cDCs. These findings are the first to show that STING is required within cDCs to mediate DNA vaccine induced Th1 immune responses and provide new insight into the mechanism whereby DNA vaccines induce Th1 responses.